Improvement of Physicochemical Properties of Cheese Whey Edible Film through Egg White Addition - Wulandari, Afiza; Juliyarsi, Indri; Melia, Sri (Jurnal Ilmu dan Teknologi Hasil Ternak, 2024)
This study aims to develop and characterize cheese whey edible film with egg white addition as an environmentally friendly packaging. Whey, a byproduct of the cheese-making process, is rich in nutrients but has not been optimally utilized. This study uses a randomized block design with 4 treatments: no egg white addition (control), and the addition of 1.5%, 3%, and 4.5% egg white, each with 5 repetitions. The results show that the addition of egg white significantly increases the thickness, solubility  time, water vapor transmission rate and protein content (p < 0.05) but has no significant effect on water content (p > 0.05). The thickness of the edible film ranges from 0.149 to 0.242 mm, solubility time from 53 to 109 seconds, water vapor transmission rate from 4.91 to 7.04 g/mm²/day, moisture content from 16.85% to 21.10%, protein content from 4.62% to 9.57%, and elongation from 30.55% to 36.90%. Based on research, adding B (1.5%) to egg whites produces the best treatment. This study demonstrates that the combination of whey and egg white can produce edible films with good physical and chemical characteristics, which can be used as an alternative packaging for food products, reducing plastic usage, and increasing the economic value of whey and egg white as waste products.